Effect of applying cow manure rates on the growth and yield of some selected onion cultivars under drip irrigation system at Eastern farm, Budaiya, Bahrain Kingdom - Elgubshawi, Dr. Abdelmoneim Ahmed (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
Onion is one of important vegetable in Bahrain Kingdom, the imported amount hit 2Mt. In accordance to sustainable agricultural development strategy of Bahrain kingdom2030, three varieties of onion (Texas, white grano and red grano) were treated by four rate of organic fertilizer (cow manure)00,8,16,24 and 32 tons /acre to promote and sustain onion yield. Bulb weight, bulb diameter, plant height, leaf length, leaf area index, biological weight and Harvest index were investigated The result showed that bulb weight, bulb diameter and leaf length were significantly affected at (p<0.05). The interaction between the treatments and the verities is significantly affected the bulb weight. the growth indicators were not responded The average production per acre at the highest application rate are,11,11,17 for the Texas, Red and White onion respectively.